(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The research aims to study the level of cortisol hormone concentration during the recovery period, specifically at 24 and 50 minutes after the competition. Many sources indicate that after physical exertion, cortisol hormone increases for two hours after the end of the effort and reaches half-life at 24 minutes after the effort. The research aims to understand the effect of physical exertion on cortisol hormone response during the recovery period at 24 and 50 minutes for pre- and post-test of Futsal players. The researcher assumes that there is a statistically significant difference in cortisol hormone response during the recovery period between 24 and 50 minutes for pre- and post-test of Futsal players. The researcher adopted a descriptive method that is suitable for the nature of the research. 14 advanced players from the Al-Allam Club for Futsal were selected, and 6 players were excluded due to their participation in the preliminary experiment and absence in the final experiment. Thus, the sample size for the study was 8 players, and the sample was matched in terms of age, training age, weight, and height.